Bilateral differences of isokinetic knee extensor strength are velocity- and task-dependent - Möck, S.; Wirth, K. (Sports Biomechanics, 2024)
The purpose of this study was to investigate the concordance of isokinetic bilateral strength differences of the knee extensors in single- and multi-joint movement tasks. One hundred and nineteen male athletes performed isokinetic legpresses at 0.1 m/s and 0.7 m/s as well as isokinetic knee extensions at 60°/s and 180°/s. Bilateral differences and directed bilateral differences (sign indicating the direction of the difference) were calculated for all measurements. Bland-Altman-Plots were plotted to investigate if the different conditions detect bilateral differences of the same magnitude. Additionally, concordance correlations for the directed bilateral differences of the different tests were calculated to investigate magnitude and direction. The results indicate poor to fair concordance between the bilateral differences in the legpress conditions as well as between single- and multi-joint tasks. The single-joint knee extensions displayed a moderate level of agreement. Bilateral strength differences in isokinetic movement tasks are dependent on movement velocity and the nature of the task (single- or multi-joint movement) in the lower extremities. Both the value and the direction of the strength differences show no clear pattern across the investigated measurements and cannot be used interchangeably. Therefore, to assess interlimb strength balance, multiple different tests should be performed.